K-Means Cluster for Grouping Regencies/Cities in South Sulawesi Province Based Human Development Index on the 2023 - Isma Muthahharah; Sitti Masyitah Meliyana; Ansari Saleh Ahmar; Abdul Rahman (ARRUS Journal of Social Sciences and Humanities, 2024)
The grouping of districts/cities in South Sulawesi province should be carried out as a material for planning and evaluating government program objectives. The aim is to increase human development figures based on the indicators that form the HDI including Life Expectancy (UHH) at birth, Expected Years of Schooling (HLS), Average Years of Schooling (RLS). Therefore, cluster analysis was used using the K-means method, which is a type of statistical analysis. This type of research is applied research with a quantitative approach by collecting and analyzing data using the K-Means Cluster method. The data used in the determination was sourced from the South Sulawesi Provincial Central Statistics Agency in 2023. The results of grouping using K-Means clusters showed that there were 3 clusters, where cluster 1 had 23 regencies/cities in the Southern Province consisting of the Selayar Islands, Bantaeng, Jeneponto, Takalar, Sinjai, Maros, Pangkep, Barru, Bone, Soppeng, Wajo, Luwu and North Luwu with low criteria. Cluster 2 has 3 regencies/cities, namely Makassar, Pare Pare and Palopo with high criteria. Cluster 3 has 8 regencies/cities, namely Bulukumba, Gowa, Sidrap, Pinrang, Enrekang, Tana Toraja, East Luwu and North Toraja with medium criteria. The suggestion in this research is that you can use indices and other methods to group districts/cities in South Sulawesi Province.